The immune response to Francisella tularensis - Barthels, Derek A.; House, Robert V.; Gelhaus, H. Carl (Frontiers in Microbiology, 2025)
Francisella tularensis (Ft) is a Gram negative intracellular bacterial pathogen, commonly transmitted via arthropod bites, but is most lethal when contracted via inhalation. The nature of a Gram-negative intracellular pathogen presents unique challenges to the mammalian immune response, unlike more common viral pathogens and extracellular bacterial pathogens. The current literature on Ft involves numerous variables, including the use of differing research strains and variation in animal models. This review aims to consolidate much of the recent literature on Ft to suggest promising research to better understand the complex immune response to this bacterium.